Anthropometric Changes in a Prospective Study of 100 Patents Requesting Breast Reduction - Lelala, Ngoato Bruce (Division of General Surgery, 2021)
Background The anthropomometry of the “ideal” breast is well described, but changes that occur with enlarged breasts are not. The aim of this study was to assess the prevalence of nipple asymmetry in the horizontal plane and changes in the inframammary fold (IMF) in patients presenting with macromastia (defined as excessive development of the mammary gland by Merriam-Webster dictionary). Methods One hundred patients (200 breasts) presenting to the Plastic Surgery Clinic for bilateral breast reduction were enrolled in this study. Patient's characteristics captured for this study included age, body mass index (BMI), and breast anthropometric measurements, such as suprasternal notch to nipple, nipple to IMF, IMF projected to cubital fossa, midhumeral point, and nipple measurement from meridian. Basic univariate statistical analysis were performed to evaluate the impact of nipple asymmetry. Results The average age was 37 years (SD 12 years), and the median BMI was 33 (IQR 28-37). More patients presented with nipple asymmetry, of whom 45% were classified as lateral to meridian, 19% were classified as medial to the meridian, and 36% were classified as central to the meridian. Patients with lateral asymmetry and medial asymmetry has a significantly higher BMI (median BMI 35) compared with patients with central positioning (median 30). Increasing breast size was positively associated with nipple asymmetry, whereas BMI (R = - 0.30, P =0.003) and macromastia correlated negatively with IMF position (R= - 0.38), P= 0.0001). Conclusion In macromastia, nipple displacement from breast meridian, especially lateral displacement, is common and is aggravated by an increase in BMI. The IMF also descends, and this is also common in patients with a raised BMI. These changes have clinical implications.